Catalytic reductions and synthesis applications of organic azides - Scrafield, Benjamin Luke (2022)
Known for over a century, organic azides are compounds of significant interest. Organic azides are potentially very useful compounds – they can be considered to function as ‘protected’ amines. In spite of certain hazards associated with these compounds, research into the chemistry of azides remains active. Chapter 1 of this thesis provides an overview of this considerable body of research in terms of the properties of organic azides, methods for their preparation, and aspects of their reactivity.